THE SOCIAL MEDIA PARADOX: NAVIGATING SELF-ESTEEM, PHUBBING, AND PROCRASTINATION IN A DIGITAL AGE - Hanani Hussin; Nurliyana Abas; Rahmat Yuliawan; Hufiza Hussin (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
The extensive usage of social media has brought immense behavioral and psychological implications, primarily on self-esteem, phubbing, and procrastination. Although there are many advantages offered by social media, including connectivity and access to information, excessive use and misuse have raised concerns about their influence on mental health and productivity. The purpose of this research is to explore the interrelatedness of self-esteem, phubbing, and procrastination and the degree to which social media usage influences these behavioral inclinations. From an extensive literature review and theoretical analysis, the research concludes some of the key causes of adverse social media consequences, such as overuse of the internet, fear of missing out (FOMO), and social comparison. The research findings indicate that addiction to social media is strongly associated with low self-esteem since people keep comparing themselves with idealized internet photos. Moreover, phubbing in the context of neglecting face-to-face interaction in favor of online interaction was discovered to negatively affect social relationships and happiness. Additionally, procrastination through social media was observed to be an increasing problem among working professionals and students, decreasing work and academic productivity. The implications of the study are theoretical and practical. Theoretically, it adds to the overall corpus of literature on the psychological and behavioral impacts of social media, extending the dialogue on social comparison theory and self-determination theory. Practically, the implications identify the necessity for awareness programs, digital wellness programs, and interventions supporting healthy social media use. These findings can be applied by educators, policymakers, and mental health practitioners to create programs that promote healthy online habits, healthier relationships, and better productivity. Long-term effects, cross-cultural differences, and possible coping strategies to offset the negative impacts of excessive social media usage must be addressed by future studies. In this way, individuals and society can move towards a healthier and more positive online environment.